If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (14 + -2)(2) = w Combine like terms: 14 + -2 = 12 (12)(2) = w Multiply 12 * 2 24 = w Solving 24 = w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1w' to each side of the equation. 24 + -1w = w + -1w Combine like terms: w + -1w = 0 24 + -1w = 0 Add '-24' to each side of the equation. 24 + -24 + -1w = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -1w = 0 + -24 -1w = 0 + -24 Combine like terms: 0 + -24 = -24 -1w = -24 Divide each side by '-1'. w = 24 Simplifying w = 24
| 403=c+273 | | 2.4+3c=0.6 | | 13x+17y=107 | | M-9m+7m+5= | | 5x(x-6)=8-9 | | y+9x=54 | | 20=6+5x+x^2 | | 4m+5=-2m-1 | | 5=13n-2 | | X-3.7=-9 | | 2x^2+kx-k^2=0 | | 14=5x+x^2 | | 12=-6*-4x-3 | | -12.1+x=14.8 | | 3r+10=22 | | X+6.4=11.3 | | 2x^2-9x=62 | | 4b-4-9b-8= | | 90+(x+20)+(x-20)=180 | | 20*5+2=a | | 4(y+4)-7y=25 | | B=13+2(9) | | 4(y-4)-7y=25 | | -2(x-7)-28=14 | | 6x-.5(4x-2)=3+11 | | -15=p-11 | | 10(5x-5)-(2x-7)= | | 6(2y-2)-(4y+4)= | | K-6=14 | | x*.035=3000 | | x*.035=2000 | | 5+4c=105 |